Structural dynamics effect on voltage generation from dual coupled cantilever based piezoelectric vibration energy harvester system - Khoo, S.Y.; Radeef, Z.S.; Ong, Z.C.; Huang, Y.H.; Chong, W.T.; Ismail, Z. (Elsevier, 2017)
This article investigates the effect of structural dynamics on voltage generation from a novel dual coupled cantilever based piezoelectric vibration energy harvester (PVEH) system. Two non-destructive vibration techniques using the EMA and ODS analysis techniques have been integrated into the location selection scheme for enhancing vibration energy harvesting purpose. The location selection scheme is based on a measurement procedure on both harvester and its host structure to identify the optimal location. The results shows that the proposed cantilever PVEH is able to harvest high voltage in the high displacement region. An optimal location, (i.e. maximum vibration points/anti-nodal points) determined by the location selection scheme could yield 33.3% improvement in harvested voltage, as compared to baseline voltage. Meanwhile, if the piezoelectric plate is placed at any minimal vibration points or nodal point on the structure as determined by the location selection scheme, a significant reduction (>70%) in harvested voltage is observed.